Auditor reporting under Section 404: The association between the internal control and going concern audit opinions - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2012)
Section 404 of the Sarbanes-Oxley Act introduced integrated audits of internal control over financial reporting and the financial statements. Since the internal control and audit reports are joint products of the audit process, we examine whether the issuance of an internal control material weakness opinion (MWO) influences, other things equal, the issuance of a going concern audit opinion (GCO). Using a sample of financially stressed companies, we find that the issuance of a MWO increases the likelihood of a GCO, suggesting that auditors respond to the uncertainty surrounding a MWO by issuing a GCO. Further, the positive association between MWO and GCO obtains for company-level material weaknesses, which are difficult to “audit around”. We compare these results with those for a Section 302 sample with manager-reported (but not audited) material weaknesses, and find that the material weakness reported under Section 302 does not impact the GCO. Hence, the auditors respond to the uncertainty surrounding material weaknesses only when they issue MWOs, and not due to the existence of material weaknesses — that is, the issuance of a MWO induces further conservatism in the auditor's GCO decision. Our findings have relevance for policymakers. Section 404 is focused on enhancing financial reporting quality, yet there has been no discussion on how it could impact the GCO decision. To the extent that the increase in the GCO likelihood is a result of auditor conservatism, our study indicates the need for an evaluation of the effects of Section 404 on the financial statement audit.